SPECT Myocardial Perfusion Imaging in the Diagnosis of Apical Hypertrophic Cardiomyopathy- Case Series and Literature Review (Bangladesh Journal of Nuclear Medicine, 2024)
Apical hypertrophic cardiomyopathy (AHCM) is a subtype of hypertrophic cardiomyopathy (HCM) in which hypertrophy mostly affects the apex of the left ventricle, resulting in mid-ventricular obstruction. The diagnosis is usually made when the LV apex has an apical wall thickness of ≥ 15 mm in echocardiography, though sometimes it is missed due to the poor acoustic window in two-dimensional echocardiography. Single Photon Emission Computed Tomography-Myocardial Perfusion Imaging (SPECT-MPI) can often detect apical hypertrophy. The apical hypertrophy was identified by SPECT-MPI in the reported three cases, which were not previously diagnosed by echocardiography.Bangladesh J. Nuclear Med. 27(1): 100-106, 2024